Anxiety Level in Students’ Public Speaking: Causes and Remedies - Zuhri, Muhammad Darrin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Madura, 2023)
Their assessments and appraisals are often not depictive of their professional competitiveness; therefore, it is important for students to overcome public speaking anxiety before they transit from academic life to professional life. The purpose of this study is to analyze the reasons behind the anxiety level in undergraduate students of a public speaking class and recommend strategies to overcome this fear. This study was entailed quantitative research paradigm on a sample of 50 students of English Department at Unira. The findings showed that students who fear public speaking can perform well if they use certain strategies to fight their fears. 75% participants admitted their fear of public speaking and 95% participants agreed that if proper counseling, instruction and coaching is provided, this fear can be overcome. Research revealed that exposure to virtual environment can facilitate student confidence and enables them to face audience irrespective of the size.